Pengaruh Kualitas Produk, Kualitas Pelayanan dan Promosi terhadap Kepercayaan Pelanggan (Konsumen) di Erha Skin Padang - Irdha Yusra; Widia Wati Rizki (Indonesian Journal of Applied Accounting and Finance, 2021)
Companies engaged in the service sector must be able to maintain a good reputation in the eyes of their customers. However, there are still many complaints that are felt by customers. This study aims to determine Product Quality, Tangibles, Reliability, Responsiveness, Assurance, Emphaty, Promotion and Customer Trust in Erha Skin Padang. The samples were determined by using the Stratified Random Sampling technique with a total of 56 customers (consumers). Data were collected through questionnaires and then analyzed statistically descriptive and Independent-Sample T-Test with the SPSS version 16 program. The results of the data analysis show that Product Quality, Tangibles, Reliability, Responsiveness and Emphasis are the main factors that determine the level of customer trust. Meanwhile, Assurance and Promotion have a less dominant contribution to customer trust